Recommendations for how to communicate bad news - Beatriz Villa López (Fundación para el Desarrollo de la Enfermería, 2007)
The communication, along with the control of the symptoms and the emotional support are the basic instruments that are used in the daily development of our profession. To be little capable at the time of notifying bad news can generate an added suffering unnecessary in the person who receives the new and a deterioration in the relation professional-patient.In many occasions, at the time of approaching these situations, the professional of the health usually feels anguish, fear and restlessness, this is because during is scared and restlessness this happens because during his stage of studies in the faculty the student has received a formation based on the binomial health-disease from a totally biological perspective forgetting the abilities communication.Supported in different bibliographical sources, this article tries to analyze the factors that influence when communicating the bad news and, to suggest some preventatives ideas on how giving them trying to prevent the burnout syndrome.